(untitled) (Revista Argentina de Musicología, 2016)
This research work studied a historical-musical process of medium duration (1880- 1910), focusing on the delimitation of a aesthetic-musical field in San Juan (Argentine), since the reception of the Italian immigrants’ music. It covered from the decade when the first news about the Italian Colecchia family are registered in San Juan, until the socio-musical changes we observe since the Centenary of May Revolution. Finding scores and personal documents of the Colecchia family originated a heuristic corpus which will in turn be transfered to custody of the Gabinete de Estudios Musicales of the Universidad Nacional de San Juan. This material, until then unexplored, raised a number of queries about its production, communication and reception in the community, that started the investigation. Therefore, the study of the story of these musicians, appropriated of their socio-cultural and historical universe and in the context of the reference and groups they belonged to, con tributes to the new history of regional music.